Practice guideline update summary: Efficacy and tolerability of the new antiepileptic drugs I: Treatment of new-onset epilepsy. Issue 4 (July 2018) - Kanner, Andres M.; Ashman, Eric; Gloss, David; Harden, Cynthia; Bourgeois, Blaise; Bautista, Jocelyn F.; Abou-Khalil, Bassel; Burakgazi-Dalkilic, Evren; Park, Esmeralda Llanas; Stern, John; Hirtz, Deborah; Nespeca, Mark; et al.
Objective: To update the 2004 American Academy of Neurology (AAN) guideline for treating new-onset focal or generalized epilepsy (GE) with second- and third-generation antiepileptic drugs (AEDs).Methods: The 2004 AAN criteria was used to systematically review literature (January 2003 to November 2015), classify pertinent studies according to the therapeutic rating scheme, and link recommendations to evidence strength.Results: Several second-generation AEDs are effective for new-onset focal epilepsy. Data are lacking on efficacy in new-onset generalized tonic–clonic seizures, juvenile myoclonic epilepsy, or juvenile absence epilepsy, and on efficacy of third-generation AEDs in new-onset epilepsy.Recommendations: Lamotrigine (LTG) should (Level B) and levetiracetam (LEV) and zonisamide (ZNS) may (Level C) be considered in decreasing seizure frequency in adults with new-onset focal epilepsy. LTG should (Level B) and gabapentin (GBP) may (Level C) be considered in decreasing seizure frequency in patients ≥60 years with new-onset focal epilepsy. Unless there are compelling adverse-effect–related concerns, ethosuximide (ETS) or valproic acid (VPA) should be considered before LTG to decrease seizure frequency in treating absence seizures in childhood absence epilepsy (Level B). No high-quality studies suggest clobazam, eslicarbazepine, ezogabine, felbamate, GBP, lacosamide, LEV, LTG, oxcarbazepine, perampanel, pregabalin, rufinamide, tiagabine, topiramate, vigabatrin, or ZNS is effective in treating new-onset epilepsy because no high-quality studies exist in adults of various ages. A recent FDA strategy allows extrapolation of efficacy across populations; therefore, for focal epilepsy, eslicarbazepine and lacosamide (oral only for pediatric use) as add-on or monotherapy in persons ≥4 years old and perampanel as monotherapy received FDA approval.